2021
DOI: 10.1042/bsr20212246
|View full text |Cite
|
Sign up to set email alerts
|

Association of m.5178C>A variant with serum lipid levels: a systematic review and meta-analysis

Abstract: Background: Emerging evidence shows that m.5178C>A variant is associated with a lower risk of coronary artery disease (CAD). However, the specific mechanisms remain elusive. Since dyslipidemia is one of the most critical risk factors for CAD and accounts for at least 50% of the population-attributable risk, it is tempting to speculate that the reduced CAD risk caused by the m.5178C>A variant may stem from an improved lipid profile. In order to verify this hypothesis, we conducted this study to cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…It also has much higher heritability when compared to IR [56], implying that environmental factors that afect IR have much less impact on HDL-C. Furthermore, many of the genetic polymorphisms that have been shown to afect HDL-C concentrations would not be expected to afect insulin resistance [57][58][59][60]. It should also be noted that, although epidemiological data show that low HDL-C is associated with increased cardiovascular disease, most known genetic variants that afect HDL-C levels do not increase cardiovascular disease risk [57,61,62].…”
Section: Discussionmentioning
confidence: 99%
“…It also has much higher heritability when compared to IR [56], implying that environmental factors that afect IR have much less impact on HDL-C. Furthermore, many of the genetic polymorphisms that have been shown to afect HDL-C concentrations would not be expected to afect insulin resistance [57][58][59][60]. It should also be noted that, although epidemiological data show that low HDL-C is associated with increased cardiovascular disease, most known genetic variants that afect HDL-C levels do not increase cardiovascular disease risk [57,61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Liu F. et al [14] findings indicate that the m.5178C > A variant is linked to elevated levels of high-density lipoprotein cholesterol (HDL-C), standardized mean difference (SMD) = 0.12, 95%, confidence interval (CI) = 0.06-0.17, p < 0.001], and total cholesterol (TC) (SMD = 0.08, 95% CI = 0.02-0.14, p = 0.01). When we examined specific populations, we found that the m.5178C > A variant was associated with increased HDL-C levels in both Japanese (SMD = 0.09, 95% CI = 0.01-0.17, p = 0.03) and Chinese (SMD = 0.13, 95% CI = 0.07-0.20, p < 0.001) groups.…”
Section: Coronary Artery Diseasementioning
confidence: 99%